SELECTION OF DEVELOPMENT ALTERNATIVES FOR FLANK AND CREST AREAS OF CHANNEL AND SUBTIDAL SHEET COMPLEX - Marno
Abstract: The principle reservoir in Kotabatak field is the Bekasap formation. The field studies and analyses of production characteristics confirm that the field is a geologically complex reservoir. It exhibits a large variation of production response across the reservoir. Changes in rock properties, faulting, and channelization of the major sands have contributed to complexity of the formation. Two basic types of reservoirs are distinguished as channelized sandstones and sub-tidal sheet sandstones. Secondary field development of Kotabatak field was driven by economics value. Because of this driver, the first secondary development was started from the highest potential reserves and lowest geological risk area. The development was expanded to the area, which has geological and reservoir performance similarity. The coverage area of expansion is mostly located at the center body of the field. Flank and crest reservoir have not been covered by this expansion and left as it is. This work focuses on the potential assessment of the flank and crest areas by considering the geological facies distribution and well-by-well performance. Numerous development alternatives are evaluated to quantify the potential reserves that could be recovered. Economic evaluation is then performed based on prediction incremental reserves. The prediction was done using 3D flow simulation numerical model. Economic figures are used as basis in defining the optimum development alternatives. Based on results of this study, the edges of the reservoir characterized by alternate channel and sub-tidal sheet facies show that a combination of denser peripheral and wide spacing pattern waterflood that consider the facies distribution during placing the wells gave the highest recovery. For the crest area dominated by channel facies, a form of peripheral flood gives significant incremental recovery over the fully pattern waterflood development. This scenario should be selected as the optimum development alternative offering the highest additional recovery and economics value.